2019
DOI: 10.1007/s00702-019-01984-3
|View full text |Cite
|
Sign up to set email alerts
|

The first identification of nesfatin-1-expressing neurons in the human bed nucleus of the stria terminalis

Abstract: Neuropeptides are involved in various brain activities being able to control a wide spectrum of higher mental functions. The purpose of this concise structural investigation was to detect the possible immunoreactivity of the novel multifunctional neuropeptide nesfatin-1 within the human bed nucleus of the stria terminalis (BNST). The BNST is involved in the mechanism of fear learning, integration of stress and reward circuits, and pathogenesis of addiction. Nesfatin-1-expressing neurons were identified for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
4
0
2
Order By: Relevance
“…A recent report showed that roughly one third of all nesfatin-1 positive neurons in the PVN as well as the Arc also express glucocorticoid receptors, which support the theory of an influence of peripheral adrenal stress signals on central NUCB2/nesfatin-1 expression [86]. Nesfatin-1 was also shown to be expressed in neurons of the BST in humans [23], which is known to be an important neuronal structure for anxiety [87], stress [88], and fear [89]. The volume of the central part of the BST is higher in men than in women [90,91].…”
Section: Potential Involvement In Stress Responsementioning
confidence: 58%
See 1 more Smart Citation
“…A recent report showed that roughly one third of all nesfatin-1 positive neurons in the PVN as well as the Arc also express glucocorticoid receptors, which support the theory of an influence of peripheral adrenal stress signals on central NUCB2/nesfatin-1 expression [86]. Nesfatin-1 was also shown to be expressed in neurons of the BST in humans [23], which is known to be an important neuronal structure for anxiety [87], stress [88], and fear [89]. The volume of the central part of the BST is higher in men than in women [90,91].…”
Section: Potential Involvement In Stress Responsementioning
confidence: 58%
“…NUCB2/nesfatin-1 is expressed in multiple tissues such as adipose tissue [14], X/Alike cells of the stomach [15,16], pancreas [17], specifically pancreatic beta-cells [18], testis [19], and the lung [20]. In the central nervous system, NUCB2/nesfatin-1 immunoreactivity was detected in various nuclei of the hypothalamus [21], piriform, cingulate, as well as insular cortex, medial preoptic area, ambiguus nucleus, nucleus accumbens (EW) [22], the bed nucleus of the stria terminalis (BST) [23], ventrolateral medulla, dorsal raphe nucleus and gigantocellular reticular nucleus, and cerebellum, as well as in autonomic sympathetic and parasympathetic preganglionic neurons of the spinal cord [21,24]. It should be noted that peripheral mRNA NUCB2/nesfatin-1 expression levels-mainly the stomach-are significantly higher than the expression in the central nervous system [16].…”
Section: Expression Sites Of Phoenixin and Nesfatin-1mentioning
confidence: 99%
“…Z kolei inny (nieoznaczany w badaniu) neuropeptyd -nesfatyna-1 może nasilać wpływ PNX-14 na uwalnianie hormonów reprodukcyjnych, takich jak LH, folikulotropina i testosteron u samców szczurów [39]. Okazuje się również, że nesfatyna-1 ulega ekspresji w neuronach jądra łożyskowego prążka krańcowego, które bierze udział w rozwoju lęku, stresu czy strachu [40]. Wobec istniejącego związku między nesfatyną-1 i PNX wskazane jest oznaczanie stężeń w dalszych badaniach nesfatyny-1 wraz z PNX i zbadanie powiązań stężeń PNX ze stężeniami nesfatyny-1.…”
Section: Omówienieunclassified
“…Nesfatyna-1 jest 82-aminokwasową cząsteczką powstałą w wyniku potranslacyjnej konwersji peptydu prekursorowego NEFA/nukleobindyny-2 (NUCB2). W mózgu szczura najsilniej zaznaczoną ekspresją nesfatyny-1 charakteryzują się neurony podwzgórza i pnia mózgu (Goebel et al, 2009), u ludzi neuropeptyd ten zlokalizowano dotychczas w podwzgórzu (Psilopanagioti et al, 2019) i jądrze łożowym blaszki krańcowej (bed nucleus of the stria terminalis, BNST) (Pałasz et al, 2019), strukturach związanych czynnościowo z mechanizmami stresu i lęku. Kilka ostatnio przeprowadzonych badań sugeruje, że ostry ograniczony stres (acute restraint stress) jest jednym z czynników aktywujących ekspresję nesfatyny-1 (Goebel et al, 2009;Stengel et al, 2010).…”
Section: Nesfatyna-1 W Zaburzeniach Lękowychunclassified
“…In the rat brain, neural populations with nesfatin-1 expression are mainly located in the hypothalamus and the brainstem (Goebel et al, 2009). Nesfatin-1 immunoreactivity was recently detected in the human hypothalamus (Psilopanagioti et al, 2019) as well as in the bed nucleus of the stria terminalis (BNST) (Pałasz et al, 2019). A few recent studies suggest that acute restraint stress is one of the factors activating the expression of nesfatin-1 (Goebel et al, 2009;Stengel et al, 2010).…”
Section: Nesfatin-1 In Anxiety Disordersmentioning
confidence: 99%